The little Kiwi's Matariki - Slade-Robinson, Nikki 1968- (Duck Creek Press, 2016)
The little Kiwi is fast asleep in her burrow. A beam of moonlight shines right down into her burrow. She wakes, and realises it is time. Hurrying out into the night, she wakes each of her friends from their midwinter slumber.'Kia tere! Hurry!' she urges them. The little Kiwi leads her friends through the pingao and onto the beach. It is pre-dawn. They wait, and watch. As the moon slips away behind the hills, the constellation of Matariki rises for the first time, in the northeastern sky. Finishes with an explanation of Matariki - its origins, traditions and how it is celebrated today. The constellation is also shown, with the Māori names for each star. The text contains some simple words in Te Reo Māori alongside the English equivalenṯ